2016
DOI: 10.1016/j.jvs.2016.05.067
|View full text |Cite
|
Sign up to set email alerts
|

The presentation and management of aneurysms of the pancreaticoduodenal arcade

Abstract: GDAAs and PDAAs are uncommon lesions that are often associated with a celiac axis stenosis/occlusion leading to altered hemodynamics in the pancreaticoduodenal arcade. These aneurysms are prone to rupture regardless of size, and intervention is accordingly recommended for all aneurysms upon recognition. Despite the concordant celiac axis obstruction and concern for maintenance of hepatic circulation, endovascular repair of these aneurysms is generally successful and should be considered as the initial operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…In our series only one patient presented with ruptured aneurysm and urgent embolization was successful. Other authors confirmed usefulness of endovascular procedures in emergent situation [ 12 , 13 ]. Suzuki et al [ 12 ] reported series of seven patients with ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In our series only one patient presented with ruptured aneurysm and urgent embolization was successful. Other authors confirmed usefulness of endovascular procedures in emergent situation [ 12 , 13 ]. Suzuki et al [ 12 ] reported series of seven patients with ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 60%
“…Follow-up studies showed spontaneous, complete thrombosis of these aneurysms. Corey et al [ 13 ] reported series of 35 patients, seven of whom presented with ruptured aneurysms. Embolization was immediately successful in all cases, but surgical ligation was required in two cases in the postprocedural period due to rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of the hepatic arterial flow is an important issue in coil embolization for aneurysms of the pancreaticoduodenal arcade. However, revascularization of the celiac artery is not required usually, because arterial flow to the liver is maintained through a patent gastroduodenal artery (GDA) [4] . When it is necessary to embolize GDA in the presence of the celiac artery occlusion, revascularization of the celiac artery including aorto-hepatic artery bypass or celiac axis stenting should be considered [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for pancreaticoduodenal artery aneurysms is therefore considered appropriate, even in asymptomatic patients. Recently, endovascular management has been considered the first-line treatment because it is highly successful [4] . When embolization of an aneurysm of the pancreaticoduodenal arcade is intended, hepatic artery flow must be preserved [4] .…”
Section: Introductionmentioning
confidence: 99%
“…These are followed by aneurysms of the hepatic artery (20%); superior mesenteric artery (6%); celiac artery (4%); gastric and gastroepiploic arteries (4%); jejunal, ileal, and colic arteries (3%); pancreaticoduodenal and pancreatic arteries (2%); gastroduodenal artery (GDA) (1.5%); and inferior mesenteric artery, at <1%. 2,3 Despite their low incidence, they should be considered important because they have a disproportionate rupture rate (25%) and significant morbidity and mortality (70%). [4][5][6] Unlike most VAAs, GDA aneurysms tend to be symptomatic.…”
Section: Introductionmentioning
confidence: 99%